Особливості формування структури середньозернистого твердого сплаву ВК6, спеченого за температури існування рідкої фази - Юрчук, М.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The paper describes the peculiarities of the formation of the medium-grained low-cobalt WC—6Co cemented carbide at temperatures of 1300, 1350, 1400, 1450, 1470, 1500, 1530, 1550, and 1750 °C which permit formulating the principles of serial production of two-phase WC—Co cemented carbides having optimal carbon – free structure.